Neuroendocrine changes in patients with spontaneous supratentorial intracerebral hemorrhage - Huttner, Hagen; Kiphuth, Ines-Christine; Teuber, Linda; Lücking, Hannes; Kloska, Stephan; Staykov, Dimitre; Kuramatsu, Joji; Mauer, Christoph; Breuer, Lorenz; Dörfler, Arnd; Köhrmann, Martin (Neurocritical Care, 2013)
Background: Neuroendocrine changes have been reported after ischemic stroke, subarachnoid hemorrhage, and brain trauma. As there are no corresponding data in patients with intracerebral hemorrhage (ICH) we analyzed various neuroendocrine parameters to investigate possible alterations in hormone profiles of patients with ICH. Methods: Twenty patients with ICH were prospectively enrolled in the study. Patients were a priori parted into two groups: Ten non-ventilated patients treated on the stroke-unit (hemorrhage volumes <20 ml, "small ICH"), and 10 ventilated patients treated on the neurocritical care unit (hematoma volumes >20 ml with possible additional ventricular involvement ("large ICH"). Neuroendocrine parameters were compared between both groups referring to reference values. The following parameters were obtained over a period of 9 days in 20 patients with spontaneous supratentorial ICH: thyrotropin, free thiiodothyronine and thyroxine, human growth hormone, insulin-like growth factor 1, luteinizing hormone, follicle-stimulating hormone, testosterone, prolactin, adrenocorticotropic hormone, and cortisol. Results: Small ICH patients were in a median 71 (54-88) years old and had a mean ICH volume of 9.5 ± 6.5 ml, whereas large ICH patients were 65 (47-80) years old and showed a mean volume of 56 ± 30.2 ml. None of the patients revealed pathological alterations for thyrotropin, free thiiodothyronine, thyroxine, human growth hormone, insulin-like growth factor 1, and testosterone. There was only a mild decrease of adrenocorticotropic hormone and cortisol on day 3 in large ICH patients. Small ICH patients showed pathologically elevated levels of luteinizing and follicle-stimulating hormone throughout the observation period. Large ICH patients showed a marked increase of prolactin that developed during the course. Conclusions: Overall, neuroendocrine changes in ICH patients are not as profound as reported for ischemic stroke or subarachnoid hemorrhage. The clinical significance of increased LH and FSH levels in small ICH is unclear, whereas elevation of prolactin in large ICH was anticipated. Future randomized controlled trials should also focus on neuroendocrine parameters to clarify the impact of possible hormonal alterations on functional outcome. © 2011 Springer Science+Business Media, LLC.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Hormone profile; Intracerebral hemorrhage; Neuroendocrine